Life Cycle Assessment of an emerging overhead line hybrid truck in short-haul pilot operation. (1st March 2022) - Hanesch, Susanne; Schöpp, Ferdinand; Göllner-Völker, Laura; Schebek, Liselotte
Abstract: In order to investigate the contribution of electromobility to climate change, green house gas (GHG) emissions of electric vehicles need to be studied in a life cycle (LC) perspective using the method of Life Cycle Assessment (LCA). Most LCA studies focus on passenger cars, but a high share of GHG emissions in the mobility sector comes from freight transport. Here we present a LCA of an emerging overhead line hybrid truck (OH truck) based on a unique database of real data from an eHighway field trial in Germany. We develop a LC transport model that includes vehicle, infrastructure and use phase of regional freight transport. The assessment of the present pilot operation is used as a reference for the evaluation of further developments using a scenario approach. As a first example, we apply the LC transport model to a scenario with realistic short-term improvements from the field trial. The comparison to freight transport with conventional trucks shows GHG savings of about 22%. From the detailed LC transport model outcomes, we derive the contributions of the vehicle and infrastructure components to GHG emissions as well as further environmental impact categories and we evaluate the operational phase, e.g. by identifying the break-even point for GHG savings in dependence of the utilization frequency. The findings can be used to identify further improvements of the OH truck technology. At the same time, our model enables a thorough investigation of future scenarios, allowing a robust comparison of possible alternatives for decarbonizing freight transport. Graphical abstract: Image 1 Highlights: Environmental favorability of emerging trucks by 22% can be shown in the near future. Our new life cycle transport model virtually covers all eHighway infrastructure data. E-mobility results improve with more eHighway users and high renewable energy share. Diesel remains main climate polluter due to hybrid operation on 10% electrified road.